Analyzing the consumers’ increasing usage of Internet to make calls through Mobile Apps over Voice (Minutes) in Bangladesh - Haque, Mohammad Shad (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.